(untitled) (Research, Society and Development, 2022)
Objective: To assess the quality of sleep on medical students, in addition to demonstrating the associated factors. Methods: A cross-sectional study carried out with students in the fifth and sixth year of the medical school, through the application of the Pittsburgh Sleep Quality Index (PSQI) and the results analyzed by the Statistical Package for Social Science (SPSS) program to establish correlations between sleep quality and the independent variables analyzed using Pearson’s chi-square test. Results: the prevalence of poor sleep quality was 63.6%. Poor sleep quality was found to be associated with female gender, memory failure, and sleep deprivation. Conclusion: Most students had poor sleep quality, which may be significantly affecting their health and educational performance, evidencing the importance of educational measures related to hygiene and sleep routine for this population.